Application of Back Massage to Decrease Pain Lavel in Elderly in Social House of Tresna Werdha Bondowoso - Mahmud Ady Yuwanto; Yugi Chandra Hari Purnama; Rizki Eko Prasetyo (Health Notions, 2018)
Back massage is a smooth movement and pressure on the surface of the skin done on the back. Back massage therapy has a variety of benefits for the body and body system where the body will experience improvement and positive effects after back massage. As for some body systems that receive positive effects of back masssage therapy are the nervous system, muscular system, skeletal system, circulatory system, respiratory system, digestive system, reproduction system, lymph nodes, and skin. With a back massage the body will feel the relaxation so that the felt nyari reduced. The purpose of this study was to determine the effect of back massage on the decrease of pain in elderly in Social House Tresna Werdha Bondowoso. The design of this study used the control group pretest-postets design. The sample size was 40 elderly. In this study back massage technique was given 3 times with a duration of 45 minutes. Statistical test using T-test with p-value of 0.00. Back masage therapy provides positive energy for the elderly where this therapy provides a sense of relaxation and comfort for the elderly so that the pain felt by the elderly decreased as a result of the technique that gives a comfortable sensation. Keywords: pain level; back massage; elderly